The Role of Linguo-Cultural Dictionaries in the Process of Language Leaners’ Values Formation - Zabolotskaya, Albina Ravilevna; Danilova, Olga Aleksandrovna (Journal of History Culture and Art Research, 2017)
At the present time the foreign language is not only a means of communication for full-fledged rendering of thoughts expressed in another language, but also the guide in the perception of the definite set of values. The study of foreign languages is a targeted process for the development of universal spiritual values and achievements of the world culture, ensuring the development of the intellectual and emotional sphere of the individual. Linguistic-cultural dictionaries can be considered as one of values formation sources. The purpose of this article is to examine the process of value formation in its orientation to the linguistic consciousness of members of a certain socio-cultural community as a basis for linguistic-cultural dictionaries. This intends study of the dependence of values of lexical units from the corresponding normative value system of nation representatives. The installation on the interpretation of strange, unknown culture is fundamentally different from the understanding of the phenomena during the communication. So the fragments of foreign culture are learned by transferring from one normative value system to another. Here we can observe the process of defamiliarization - the identification of unexpected, strange in comparison with the usual ways of the world discovery together with the identification of an unknown, unfamiliar with a known, traditional.